Critique of: “The Dynamic Synthesis Theory of Motivation” - Brenner, Michael E. (Management Science, 1968)
Comments on Gunn, B. 1968. The dynamic synthesis theory of motivation. Management Sci. 14(10, June) B-601–B-619.